Metodología para la aplicación de buenas prácticas y procedimientos de ISO 37001 en la gestión empresarial. - Benítez Bravo, Álvaro Gabriel (2024)
ISO 37001 is an international standard that establishes a management system designed to help organizations prevent, detect, and address bribery in their operations and value chains. It applies to any organization, regardless of size, sector, or location. This standard provides a framework for developing policies, procedures, and controls to combat bribery, promoting a culture of ethics and compliance. Corruption and bribery represent significant challenges for public or private companies worldwide, affecting their reputation and financial sustainability. In this context, a methodology is needed to assess and diagnose the level of compliance with ISO 37001 and to provide a solid framework to establish the parameters and guidelines for the formation of the ethics committee as well as a manual of good practices and procedures for the implementation of ISO 37001 in companies and their management. Globalization and increasingly competitive business environments have led organizations to focus on implementing international standards that allow them to operate transparently and efficiently. In this context, ISO 37001:2016 emerges as an essential tool to combat bribery and promote a culture of business integrity by applying a methodology of good practices and procedures required by ISO 37001 in business management, highlighting its impact on organizational sustainability and reputation.